Analysis of Production and Consumption in Hair Artisans at Karangbanjar Village, Bojongsari District, Purbalingga - Arifin, Agus; Suprapto, Suprapto (JEJAK: Jurnal Ekonomi dan Kebijakan, 2015)
Hair craft product is selected as a specialized one in Karangbanjar village,Â  Purbalingga Regency. This product has comparative advantage among other regions such as in Demak, Sragen, Karanganyar, and Brebes. It is also the second best product in the world after Guangzhou, China. This hair craft creative industry can employ many workers and generate income for the artisans in fulfilling their basic needs. The purpose of this study is to identify internal and external factors and analyze production activity and consumption behaviour of entrepreneurs of hair creative industry in Karangbanjar, Purbalingga. This study used primary and secondary data. The primary one was collected from respondentsâ€”68 entrepreneurs of hair production industry, and the secondary one was from relevant government institutions. Some measurements were applied in this study. Internal and External factors were identified by using SWOT analysis, while production activity was measured by profit analysis and economic efficiency analysis, and the consumption was measured by average propensity to consume (APC) analysis. The result shows that: 1) Hair creative industry has strenghts over weaknesses and opportunities over threats; (2) Hair creative industry offers high profit; 2) The entrepreneur profit coming from this industry can fulfill most of the consumption.